Determinants of Auditor management in Detecting Fraud in the Education Sector: Empirical Study on Public Accounting Firm - Prayudha, Dimas; Widodo, Condro (The Faculty of Education and Teaching Training, 2025)
This study aims to examine the determinants of auditor management in detecting fraud within the education sector, specifically analyzing the influence of audit delay, audit fee, whistleblowing system, and workload through the lens of attribution theory. The empirical object of the research comprises auditors working at public accounting firms in Surabaya, Indonesia. Employing a quantitative approach, primary data were gathered through the distribution of structured questionnaires to 109 auditors across 55 accounting firms. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method, version 4.00. The findings reveal that audit delay, audit fees, and workload exert a significant positive effect on auditors’ ability to detect fraud. Conversely, the whistleblowing system does not show a statistically significant impact. These results suggest that longer audit engagement periods, sufficient financial incentives, and increased workload intensity may enhance auditors’ diligence and cognitive alertness in identifying fraudulent practices within educational institutions. However, the whistleblowing mechanism appears underutilized or insufficiently integrated into audit procedures. This study contributes theoretically by reinforcing the applicability of attribution theory in the context of audit decision-making. From a practical perspective, the findings encourage public accounting firms to optimize auditor workload distribution, ensure fair audit compensation, and enhance the operational effectiveness of whistleblowing systems as complementary tools in fraud detection processes within the education sector.